Проблема значения речи в фатической функции - Драздаускене, Мария-Людвика (Kalbotyra, 1983)
The paper focusses on differences in the treatment of meaning in the phatic function or speech. The argument derives from the fundamental works on the phatic function and phatic communion by major authors. Although it is admitted that the phatic function, not even implying sociability, is not entirely impossible, this function is shown to expose the potential of meaning essentially determined by social factors and cultural tradition.